Phenomenological inquiry into Southern Chinese Floral Ornamentations’ cultural meanings in Melaka’s late straits-eclectic architecture - Zakaria, Abdul Hakim; Azmin, Aida Kesuma (Faculty of Built Environment, Universiti Malaya, 2026)
Under the background of tourism development, the quality of many architectural heritages gradually deteriorated. The historical atmosphere and traditional culture of original place are increasingly losting. It makes unique memory of residents disappear, and also makes the satisfaction of tourists decline. Finally, the tension between people and place is caused. To solve this problem, place theory on the relationship between people and place is constantly evolving, which can help people to establish and enhance sense of place. However, researches on sense of place are distinctive in different disciplines. Therefore, based on WOS and CNKI databases, this study reviews some key researches on sense of place by systematic literature review from concept discrimination, dimension division, generation process and influencing factors. And a theoretical framework is finally given to understand sense of place in the context of architectural heritage. The research significance is to guide to enhance sense of place in architectural heritage.